ANALISIS HUBUNGAN AUDITOR-KLIEN: FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2009-2013) - Anantyo Hartono, Tito; Rohman, Abdul (Diponegoro Journal of Accounting, 2015)
The  main  purpose  of this research  is examining  factors that affect  the audit firm switching. Those factors are change in management, qualified audit opinion, client size, audit quality, audit  fee,and audit delay. Some of past researches regardless auditor   switching, shows different results. Therefore, another research needs to be done to verify theory of auditor switching.The data being used is from manufacturing company which is listed in “Bursa Efek Indonesia” (BEI) in 2009-2013 period. Research variable being used are Change in Management (CEO), Qualified Audit Opinion (OPINI), Client Size (LnTA), Audit Quality (AQ), Audit Fees (FEE), Audit Delay (AUDELAY) and Auditor Switching (SWITCH). By using logistic regression in SPSS 16 software, this research tried to test effect of Change in Management,Qualified Audit Opinion,Client Size,Audit Quality,Audit Fees,Audit Delay towards Auditor Switching.Result of this research is that client size,and audit delay have significant effect on auditor switching in Indonesia. While other variables in this reserach like change in management, qualified audit opinion, audit quality, audit fee do not have significant effect to auditor switching in Indonesia.